Obesity and the Effects of Excess Adiposity on Bone Properties, Health, and Function - Lisa Anne Taylor (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
This article aims to inform on the relationships that exist between obesity, a fairly modern ailment to the human species, and bone mechanical properties and function. Because the phenomenon that is obesity is so contemporary, it’s progressive effects on the skeletal system are poorly understood. Many previous studies aimed to prove that obesity had a positive effect on bone mass. It was believed that obesity and the excess body mass attributed to it essentially increased BMD by presenting load bearing bones with higher levels of stress than their non-obese counterparts, but this assumption of a positive correlation seems to be confounded by a variety of biological and endocrinological factors. The following sections will explore the effects that diets high in saturated fats and its consequence, obesity, have on the absorption of dietary calcium. This flaw in the absorption of dietary calcium may mean the decreasing ability of bone, particularly trabecular bone, to maintain proper density and in turn, become increasingly brittle. Combined with the increase in mechanical loading regimes that excess adiposity may present weight-bearing bones with, an understanding of these combined effects on bone biology is pivotal. This paper will also explore the relationships that exist between obesity, serum leptin levels and inflammatory responses, and bone properties. All of these factors (calcium absorption, leptin, and inflammatory responses) are important for bone growth, function, and mechanics, especially in respect to senescence. The previously mentioned “side effects” of obesity are also recognized as factors in the initiation of osteoporosis. Consequently, there must exist a relationship between obesity and osteoporosis. The bulk of this article will further explore this refined relationship in order to prove that the effects of obesity are indeed deleterious to health, and ultimately, to the function of bone as well.